Menyuap Nasi, Mencerna Memori: Memori Kolektif Hongeroedeem - Galuh Ambar Sasi (Lembaran Sejarah, 2014)
Javanese families usually say nek mangan dienthekke, ndak pithikke mati to persuade their children to finish their food when they eat. Slightly different sentence is found in the villages of southern Purworejo; nek mangan dienthekke, elinga zaman odhim. Base on ithe nterview sources, it is known that it represents collective memory of starvation in the green revolution era.